Retinal Microvascular Changes in Subtypes of Ischemic Stroke - Zhao, Ying; Yang, Bing; Xu, An-Ding; Ruan, Yi-Wen; Xu, Ying; Hu, Hui-Ling; Tan, Ze-Feng (Frontiers in Neurology, 2021)
Aims: Retinal microvasculature shares prominent similarities with the brain vasculature. We aimed to assess the association between retinal microvasculature and subtypes of ischemic stroke. Method: We consecutively enrolled ischemic stroke patients within 7 days of onset, who met the criteria of subtype of atherothrombosis (AT), small artery disease (SAD), or cardioembolism (CE) according to a modified version of the Trial of Org 10172 in Acute Stroke Treatment (NEW-TOAST). Digital fundus photographs were taken within 72 hours of hospital admission using digital camera (Topcon TRC-50DX) , and fundus photographs were semi-automatically measured by softwares (Canvus 14 and NeuroLucida) for retinal vasculature parameters. Results: A total of 141 patients were enrolled, including 72 with AT, 54 with SAD, and 15 with CE. AT subtype patients had the widest mean venular diameter within 0.5-1.0 disk diameter (MVD0.5-1.0DD) followed by SAD and CE subtype (86.37±13.49 vs. 83.55±11.54 vs. 77.90±8.50, respectively, P=0.047); CE subtype patients had the highest mean arteriovenous ratio within 0.5-1.0 disk diameter (MAVR0.5-1.0DD) followed by the AT and SAD subtype-groups (0.97±0.03 vs. 0.89± 0.99 vs. 0.89 ±0.11, respectively, P=0.010); SAD subtype patients were found with the highest mean venular tortuosity within 0.0-2.0 disk diameter (MVT0.0-2.0 DD) followed by the AT and CE subtype (1.0294±0.0081 vs. 1.0259±0.0084 vs. 1.0243±0.0066, respectively, P=0.024). After adjusting for clinic characteristics, MVD0.5-1.0DD was significantly different among AT, SAD and CE subtypes (P=0.033). By receiver operating characteristic curve analysis, MVD0.5-1.0DD predicted the AT subtype (area 0.690, 95% confidence interval , 0.566-0.815), with a cutoff value of 82.23 μm (sensitivity 61.1%, specificity 73.3%). Conclusion: Retinal MVD 0.5-1.0DD (>82.23 μm) might associated with AT stroke subtype, however, we need large scale prospective studies in future to explore the underling mechanism and causal explanation for this finding.